Business incubation as a tool for transforming MSMEs in the Tanzanian tourism sector - Batinoluho, Ladislaus (Hotel and Tourism Management, 2023)
The failure of the majority of start-ups in the Tanzanian tourism sector is mainly due to the inadequate business incubation services in the country. Through qualitative method, this study suggests a model for establishing tourism incubation centres in Tanzania with a pilot in Arusha, Dar es Salaam and Zanzibar. An initial three-year implementation needs to be considered and it will require strong collaboration and cooperation among different stakeholders, working together to support and grow tourism MSMEs in the country. This study will guide the adaption of the business incubation approach in the tourism sector. Business incubation will contribute to a broader goal of establishing, sustaining and developing tourism MSMEs that will lead to economic prosperity in Tanzania. The study is an early wake up call for policy and decision makers to consider adapting business incubation as a tool for transforming MSMEs in the tourism sector in Tanzania.